Continuous contractional deformation followed by extension in the Nowy Sącz Basin, Polish Outer Carpathians: constraints from fault-slip analysis - Fodor, László; Świerczewska, Anna; Strzelecki, Piotr J. (Geology, Geophysics and Environment, 2025)
Fault-slip analysis was carried out in the Nowy Sącz Basin and the surroundings of the Polish Outer Carpathians based on field observations, published maps, and publications. A reconstruction of the stress field and the contractional directions from the folds suggests that the area was marked by four different deformation phases, most of them involving several stress states. The tilt test supports the separation of pre-, syn-, and post-folding deformation episodes within the phases which occurred during the folding of the Palaeogene to Early Miocene flysch units and also during the folding of the late Middle Miocene basin fill. After an early extensional phase at the onset of the deformation history, the area was marked by contractional deformation from 34 Ma to 8 Ma. During this period the compressional direction did not change markedly but a slight clockwise change of the maximal stress axis may have occurred in the Early Miocene due to vertical-axis block rotation. In this persistent deformation field, the basin could have had a contractional origin in front of an out-of-sequence thrust. The latest Miocene(?) to Quaternary deformation was probably related to the extensional collapse of the Carpathian accretionary wedge.